Visible and near infrared fluorescence spectral flow cytometry. Issue 3 (6th December 2012) - Nolan, John P.; Condello, Danilo; Duggan, Erika; Naivar, Mark; Novo, David
Abstract: There is a long standing interest in measuring complete emission spectra from individual cells in flow cytometry. We have developed flow cytometry instruments and analysis approaches to enable this to be done routinely and robustly. Our spectral flow cytometers use a holographic grating to disperse light from single cells onto a CCD for high speed, wavelength‐resolved detection. Customized software allows the single cell spectral data to be displayed and analyzed to produce new spectra‐derived parameters. We show that familiar reference and calibration beads can be employed to quantitatively assess instrument performance. We use microspheres stained with six different quantum dots to compare a virtual bandpass filter approach with classic least squares (CLS) spectral unmixing, and then use antibody capture beads and CLS unmixing to demonstrate immunophenotyping of peripheral blood mononuclear cells using spectral flow cytometry. Finally, we characterize and evaluate several near infrared (NIR) emitting fluorophores for use in spectral flow cytometry. Spectral flow cytometry offers a number of attractive features for single cell analysis, including a simplified optical path, high spectral resolution, and streamlined approaches to quantitative multiparameter measurements. The availability of robust instrumentation, software, and analysis approaches will facilitate the development of spectral flow cytometry applications. © 2012 International Society for Advancement of Cytometry